(untitled) (Research, Society and Development, 2022)
Introduction: the pandemic, due to its severity and number of victims in the world, has become a current topic and much debated in scientific content, since its consequences and impacts have reached several sectors. With the advance of the Covid-19 virus, restrictive measures had to be stricter, which had an impact on the closing of non-essential services, in which schools and universities that had to seek teaching alternatives in the face of isolation and all pandemic turmoil. Given this context, most higher education institutions used the method of remote classes so as not to interrupt learning. Objective: to show the changes and innovations carried out in universities to add emergency remote teaching. Methodology: A bibliographic research was carried out in which data collection took place in scientific articles, books, magazines, annuals and periodicals. Development: In the period of the pandemic, the use of the technological means to guarantee teaching is evident, in which tools such as: video classes, online lectures, Microlearning, Virtual Learning Environments, are the highlights of this modality, as it is already one of the methods applied in distance learning. Discussion: the innovations carried out during the pandemic period can be considered a differential for the study of university students, with the ability to interact through smartphones, which in turn, favor and facilitate access to digital content. Conclusion: Investment in technology and innovations are essential for the growth of the distance learning method, which facilitated access in the transition to the emergency remote teaching period.